One-step reconstruction with a 3D-printed, biomechanically evaluated custom implant after complex pelvic tumor resection. (2nd January 2015) - Wong, K. C.; Kumta, S. M.; Geel, N. V.; Demol, J.
Abstract: Resection of a pelvic tumor is challenging because of its complex three-dimensional (3D) anatomy and deep-seated location with nearby vital structures. The resection is technically demanding if a custom implant is used for reconstruction of the bone defect as the surgeon needs to ensure the resection margin is sufficiently wide and the orientation of intended resection planes must match that of the custom implant. We describe a novel workflow of performing a partial acetabular resection in a patient with pelvic chondrosarcoma and reconstruction with a custom pelvic implant in a one-step operation. A multi-planar bone resection was virtually planned. A computer-aided design implant that both matched the bone defect and biomechanically evaluated was prefabricated with 3D printing technology. The 3D-printed patient-specific instruments (PSIs) were used to reproduce the same planned resection. The histology of the tumor specimen showed a clear resection margin. The errors of the achieved resection and implant position were deviating (1–4 mm) from the planned. The patient could walk unaided with a good hip function. No tumor recurrence and implant loosening were noted at 11 months after surgery. The use of this novel CT-based method for surgical planning, the engineering software for implant design and validation, together with 3D printing technology for implant and PSI fabrication makes it possible to generate a personalized, biomechanically evaluated implant for accurate reconstruction after a pelvic tumor resection in a one-step operation. Further study in a larger population is needed to assess the clinical efficacy of the workflow in complex bone tumor surgery.